2017
DOI: 10.21743/pjaec/2017.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Residue in Milk and Milk Products: Mini Review

Abstract: Livestock is an important sub-sector of agriculture that plays a key role in economy of a country by contributing to GDP (Gross Domestic Product) and in total export. Pakistan is the 5 th largest milk producer in the world with a total milk production of about 46.44 billion liters per anum. Almost 68% milk is produced by buffalo and 27% by cow. Pesticides used in agriculture sector may transfer to animal bodies through feed and fodder. A pesticide found in water is another source of residues in milk through dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…The general finding pattern in the present survey is almost similar (but at lower levels) as showed for the other previous studies as in Egypt and Libya [13,21] as well as the reviewed data mentioned and reported [22]. For the other milk types (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The general finding pattern in the present survey is almost similar (but at lower levels) as showed for the other previous studies as in Egypt and Libya [13,21] as well as the reviewed data mentioned and reported [22]. For the other milk types (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, human beings may be chronically exposed to these persistent substances through dietary intake. Obviously, pesticides are known to cause a wide range of toxic effects and are potential source of severe health risks [15]. Many authors have already revealed the presence of such pesticides in animal products although more in developing countries [5] and [15].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, pesticides are known to cause a wide range of toxic effects and are potential source of severe health risks [15]. Many authors have already revealed the presence of such pesticides in animal products although more in developing countries [5] and [15]. However, that doesn't mean additives are the main route of contamination but it should not be excluded as it was less documented so far.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, human beings may be chronically exposed to these persistent substances through dietary intake. Obviously, pesticides are known to cause a wide range of toxic effects and are potential source of severe health risks [23]. Many authors have already revealed the presence of such pesticides in animal products although more in developing countries [9] and [23].…”
Section: Number Of Residues Per Samplementioning
confidence: 99%
“…Obviously, pesticides are known to cause a wide range of toxic effects and are potential source of severe health risks [23]. Many authors have already revealed the presence of such pesticides in animal products although more in developing countries [9] and [23]. However, that doesn't mean additives are the main route of contamination but it should not be excluded as it was less documented so far.…”
Section: Number Of Residues Per Samplementioning
confidence: 99%